Avaliação da estabilidade e da toxicidade pré-clínica de uma proteína isolada de sementes de noni (Morinda citrifolia L.), como etapas preliminares para seu uso terapêutico em humanos - Costa, Andrea Santos (2016)
Morinda citrifolia L. (noni) is a medicinal plant that has been reported to have a broad range of health benefits for cancer, infection, hypertension and inflammation. Previous reports have demonstrated that a lipid transfer protein isolated from Morinda citrifolia L. seeds, named McLTP1, displays anti-inflammatory activity in mice when administered by oral route, suggesting that this protein has potential to act as a new active principle for the development of an anti-inflammatory drug. McLTP1 was isolated from the noni seed meal through trichloroacetic acid (2.5%) precipitation and ultrafiltration. In this work, we carried out a storage stability and toxicity study of the McLTP1 and investigated its capacity to reach the systemic circulation, as well as its duration of the antinociceptive effect after oral administration. The McLTP1 storage for 1, 3 and 6 months at -20, 4 and 25 ° C, protected from light incidence, did not change its appearance, suspension, secondary structure and antinociceptive activity. McLTP1 prove to be capable of reaching a systemic circulation being detected up to 12 hours after the administration and maintaining its antinociceptive effect at the same time. There was neither significant change in mice’s gross behavior and toxicity signs throughout the experimental period (single and repeated dose). Mice body weight as well as haematological, biochemical and histopathological parameters were not affected by daily administration of McLTP1 (8mg/kg). It was not found any sign of cytotoxicity using cell line of human hepatocarcinoma (HepG2/C3a). In conclusion, these results contribute to the safety assessment of McLTP1 for human use in treatment of inflammation and pain.